A revista Chácara e Quintaes e as plantas alimentícias na virada do século XX no Brasil - Silva, Stela Maria Vieira da (2018)
This work was prompted by the question of what was eaten of vegetables in the nineteenth and early twentieth centuries. The initial studies were by the descriptions of travelers portrayed the culture of indigenous peoples, the colonial period and its ingredients and appropriations of these elements carried out by the Portuguese. As studies have been done through analyzes that portray science in Brazil in the figure of Theodoro Peckolt, renowned pharmacist of the imperial period who recorded among other plants, some indigenous habits and their food. The periodical Chácaras and Quintaes was an important record of agricultural practices and twentieth-century modifications reinforced by food precepts in the work of Eulália Vaz. By means of bibliographical research the beginning of the process of horticultural food reduction is perceived